Development of Law for the Management Supervision of the Developed-Estate Juristic Person - เพียรวัฒนะกุลชัย อนันต์ (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
This research has objectives to study regarding management of housing estate juristic person, in the issue of defining the offence and qualifications of housing estate juristic person, and housing estate juristic person president and board of directors regarding management of housing estate juristic person. This research also studies about the right and duty of members or buyers of allocated land. The researcher used the Condominium Act, B.E. 2522 (1979) to compare and study, used the documentary research technology, studied, collected, searched and synthesized Thai and foreign legal documents. From studying, it was found that the Land Allocation Act, B.E.2543 (2000), there was no defining of offence and qualifications of housing estate juristic person, and housing estate juristic person president and board of directors, in case the persons perform their duties corruptly which is different from the Condominium Act, B.E. 2522 (1979) which defined the duties of the condominium juristic person, manager and board of directors strictly to prevent corruption in duty. Therefore, it resulted in problems in the management of housing estate juristic person. Defining of the right of members, or buyers of allocated land is the defining of right in the articles of association of housing estate juristic person which the housing estate juristic person of each area will define the right of members by themselves. Therefore, there is lack of legal certainty, or lack of central standard, or minimum legal measures. So it is recommended that improvement of the Land Allocation Act, B.E. 2543 (2000) should be made, regarding offence and qualifications of the housing estate juristic person board of directors and it is appropriate to define the right of members or buyers of allocated land in the Land Allocation Act, B.E. 2543 (2000), replacing that each housing estate setting its own right.